Parametric Study of the Rectangular Microstrip Antenna using Cavity Model - W. Salman, Jamal; M. Ameen, Mudhaffer; O. Hassan , Star (Journal of Engineering and Sustainable Development, 2006)
A cavity model well suited for computer aided design is presented and developed tostudy the rectangular microstrip antenna. The patch is described by geometrical andelectrical parameters. The resonant frequency, resonant resistance, bandwidth, efficiencyand other electrical parameters of RMSA have been presented as a function of varyingthe patch dimension and substrate parameters. The accuracy and usefulness of themethod are investigated through comparison with experimental results as well as otherprevious theoretical methods.